Effect of Intensive Face Yoga on Facial Muscles Tonus, Stiffness, and Elasticity in Middle-Aged Women: A Pre-Experimental Clinical Trial - Hazel Çelik Güzel; Şule Keçelioğlu; Ahmet Kurtoğlu; Safaa M. Elkholi (Medicina)
Background and Objectives: The effects of face yoga, which continues to be popular as an anti-aging technique, on facial muscles in relation to aging represent an area of interest. The aim of this study was to investigate the effect of 8 weeks of intensive face yoga on facial muscles’ tonus, stiffness, and elasticity in middle-aged women. Materials and Methods: Twelve female participants with a mean age of 49.75 ± 3.76 were included in this pre-experimental clinical trial. Face yoga was applied to the participants for 8 weeks, 2 days a week face-to-face, and 5 days a week as a home program. At the beginning and the end of 8 weeks, the tonus, stiffness, and elasticity of the participants’ facial muscles were evaluated with the Myoton®PRO device. Results: Following the face yoga program, the tonus and stiffness of the frontalis (p = 0.008, p = 0.002), corrugator supercilii (p = 0.008, p = 0.019), orbicularis oculi (p = 0.023, p = 0.034), and orbicularis oris (p = 0.007, p = 0.015) muscles decreased significantly, while the tonus and stiffness of the buccinator (p = 0.008, p = 0.002) and digastric (p = 0.008, p = 0.023) muscles increased. Elasticity values increased in all evaluated facial muscles (p = 0.045, p = 0.045, p = 0.034, p = 0.023, p = 0.028, p = 0.005, respectively). Conclusions: The results reveal that face yoga has different effects depending on the physiological structure and function of the muscles and positively affects connective tissue. Future studies should reproduce the results presented here to further our understanding of the effects of face yoga.